Childhood Internalizing Symptoms Are Negatively Associated with Early Adolescent Alcohol Use. (21st May 2014) - Edwards, Alexis C.; Latendresse, Shawn J.; Heron, Jon; Cho, Seung Bin; Hickman, Matt; Lewis, Glyn; Dick, Danielle M.; Kendler, Kenneth S.
<x xml:space="preserve">Abstract</x> Background The relationship between childhood internalizing problems and early adolescent alcohol use has been infrequently explored and remains unclear. Methods We employed growth mixture modeling of internalizing symptoms for a large, population‐based sample of U.K. children (the Avon Longitudinal Study of Parents and Children Cohort) to identify trajectories of childhood internalizing symptoms from age 4 through age 11.5. We then examined the relationship between membership in each trajectory and alcohol use in early adolescence (reported at age 13.8). Results Overall, children experiencing elevated levels of internalizing symptoms were less likely to use alcohol in early adolescence. This finding held true across all internalizing trajectories; that is, those exhibiting increasing levels of internalizing symptoms over time, and those whose symptoms desisted over time, were both less likely to use alcohol than their peers who did not exhibit internalizing problems. Conclusions We conclude that childhood internalizing symptoms, unlike adolescent symptoms, are negatively associated with early adolescent alcohol experimentation. Additional studies are warranted to follow up on our preliminary evidence that symptoms of phobia and separation anxiety drive this effect.